HUBUNGAN FAKTOR LINGKUNGAN TERHADAP PRODUKSI SERASAH MANGROVE TELING TOMBARIRI, TAMAN NASIONAL BUNAKEN - Langi, Martina A.; Nurmawan, Wawan (RISALAH KEBIJAKAN PERTANIAN DAN LINGKUNGAN Rumusan Kajian Strategis Bidang Pertanian dan Lingkungan, 2023)
This study aims to compare ecosystem productivity based on litter production rate associated with tree species and climate parameters in the Teling Tombariri Mangroves, Bunaken National Park, North Sulawesi. Litter collection was carried out for 12 months in the three main mangrove constituent zones, the litter was then analyzed based on fraction and type. Litter production was then correlated with rainfall, ambient temperature, and humidity using a simple correlation coefficient. Linear correlations between monthly litter production of leaf, twig, fruit-flower fractions (reproductive fraction) of each mangrove species and monthly climate parameters (temperature, rainfall, and humidity) were calculated using Pearson’s correlation p<0.01. The results showed that the litter production rate in the Teling Tombariri Mangrove of Bunaken National Park was highest for the type Sonneratia alba, followed by Rhizophora apiculata, and finally Bruguiera gymnorhiza. The largest litter fraction was the leaf component, followed by twigs and reproductive components (flowers and fruit), except in Sonneratia alba where the reproductive component fraction was higher than the twig component. Furthermore, the environmental factor that shows the strongest correlation with litter production is rainfall, and this applies to the three main types of Teling Tombariri mangroves.